Peran Ninik Mamak Sebagai Komunikator Budaya Dalam Pembagian Hak Waris Pada Sistem Matrilineal Di Keluarga Minangkabau - Nada Aprilly Permata; Priatna Priatna (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The Minangkabau matrilineal system places women as the heirs of lineage and managers of inheritance called Harta Pusako Tinggi. The Ninik Mamak serves as a cultural communicator who regulates and conveys inheritance rights to nieces and nephews according to customary law or Islamic law, while also preventing conflicts among heirs. This system distinguishes Harta Pusako Tinggi, inherited following customary inheritance law, from Harta Pusaka Rendah, which follows Islamic inheritance law. This study examines how the cultural communication role of Ninik Mamak contributes to preserving the matrilineal customs, strengthening family harmony, and maintaining Minangkabau values amid social changes. The research aims to understand the role of Ninik Mamak as a cultural communicator in resolving inheritance conflicts within the Minangkabau community. It also explores the challenges faced by Ninik Mamak in facilitating communication and deliberation among heirs. The methodology used is qualitative descriptive, involving discussions and interviews to explore experiences and meanings of the cultural communication process. The results show that the matrilineal system protects women through Harta Pusako Tinggi, and the role of Ninik Mamak is effective in upholding customs and family harmony. Although ownership of property is held by women, control remains with men or Ninik Mamak.